2015
DOI: 10.1007/s11250-015-0818-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of extended spectrum β-lactamases/AmpC β-lactamases and plasmid-mediated quinolone resistance in Escherichia coli isolates obtained from bovine carcasses in Mexico

Abstract: Food-borne bacterial infections have worldwide importance, and a great variety of antibiotic resistance mechanisms, mainly of the chromosome type, have rapidly developed. Antimicrobial resistance was determined in this study in terms of the presence of extended-spectrum β-lactamases (ESBLs), plasmid AmpC β-lactamases (pAmpC), and plasmid-mediated quinolone resistance (PMQR) from 155 Escherichia coli isolates obtained from bovine carcasses from two states in Mexico (states of Mexico and Jalisco). Isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Moreover, the only AmpC β-lactamase encoding gene was the CMY ampC β-lactamase. This gene was previously reported in poultry ( Dierikx et al, 2013 ; El-Shazly et al, 2017 ) as well as in food producing animals ( Sato et al, 2014 ; Aguilar-Montes de Oca et al, 2015 ) and healthy pets ( Donati et al, 2014 ; Liu et al, 2016 ). As per the phenotypic and genotypic detection of AmpC production, these showed that there are some strains that were negative with the ampC disk test but positive for an ampC β-lactamase gene and vice-versa.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the only AmpC β-lactamase encoding gene was the CMY ampC β-lactamase. This gene was previously reported in poultry ( Dierikx et al, 2013 ; El-Shazly et al, 2017 ) as well as in food producing animals ( Sato et al, 2014 ; Aguilar-Montes de Oca et al, 2015 ) and healthy pets ( Donati et al, 2014 ; Liu et al, 2016 ). As per the phenotypic and genotypic detection of AmpC production, these showed that there are some strains that were negative with the ampC disk test but positive for an ampC β-lactamase gene and vice-versa.…”
Section: Discussionsupporting
confidence: 57%
“…In isolated E. coli , qnr A and qnr B detected in 33.3% of isolates, all nalidixic acid and/or ciprofloxacin resistant isolates harboured both genes. While qnr B and qnr S were identified in 10.4% of nalidixic acid resistant E. coli isolated from Algerian retail chicken meat [ 44 ] and in 10.0% of E. coli isolates obtained from bovine carcasses in Mexico [ 58 ]. In contrast, qnr A, qrn B and qrn S genes could not be identified in enrofloxacin-resistant E. coli strains from poultry in Mexico [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A positive control DNA from previously characterized E. coli isolates ( bla TEM +, bla CMY +, qnrA +, qnrB+ ) (Aguilar‐Montes de Oca et al . ) and a negative control DNA from Salmonella Typhimurium (ATCC 14028) were used.…”
Section: Methodsmentioning
confidence: 99%